A new power xgamma distribution: statistical properties, estimation methods and application - Boudjerda, Khawla (Statistics, Optimization & Information Computing, 2024)
This paper introduces a novel probability distribution called the power xgamma distribution. We investigate several statistical properties essential for its characterization, including moments, moment generating function, quantile function, and order statistics. Estimation methods are explored to determine the parameters and characteristic functions of this distribution through a comprehensive simulation study. To illustrate its practical applicability, a real-world data example is provided, which demonstrates the effectiveness and relevance of the proposed model in empirical contexts.